2024
DOI: 10.3390/antibiotics13040295
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Carbapenemase-Producing Enterobacterales in African Countries: Evolution and Current Burden

Edgar-Costin Chelaru,
Andrei-Alexandru Muntean,
Mihai-Octav Hogea
et al.

Abstract: Antimicrobial resistance (AMR) is a worldwide healthcare problem. Multidrug-resistant organisms (MDROs) can spread quickly owing to their resistance mechanisms. Although colonized individuals are crucial for MDRO dissemination, colonizing microbes can lead to symptomatic infections in carriers. Carbapenemase-producing Enterobacterales (CPE) are among the most important MDROs involved in colonizations and infections with severe outcomes. This review aimed to track down the first reports of CPE in Africa, descri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 194 publications
0
1
0
Order By: Relevance
“…ISEcp detected upstream of the bla CTX-M genes in some of the isolates is responsible for the mobilization event and increases the level of resistance [51]. The studies carried out in Africa also found CRKP and CRAB to be the most frequent MDR pathogens in ICUs [52]. In the African study, no molecular analysis of resistance genes was carried out.…”
Section: Discussionmentioning
confidence: 97%
“…ISEcp detected upstream of the bla CTX-M genes in some of the isolates is responsible for the mobilization event and increases the level of resistance [51]. The studies carried out in Africa also found CRKP and CRAB to be the most frequent MDR pathogens in ICUs [52]. In the African study, no molecular analysis of resistance genes was carried out.…”
Section: Discussionmentioning
confidence: 97%